A 2000 Year Saharan Dust Event Proxy Record from an Ice Core in the European Alps. Issue 23 (13th December 2019) - Clifford, Heather M.; Spaulding, Nicole E.; Kurbatov, Andrei V.; More, Alexander; Korotkikh, Elena V.; Sneed, Sharon B.; Handley, Mike; Maasch, Kirk A.; Loveluck, Christopher P.; Chaplin, Joyce; McCormick, Michael; Mayewski, Paul A.
Abstract: Dust events originating from the Saharan desert have far‐reaching environmental impacts, but the causal mechanism of magnitude and occurrence of Saharan dust events (SDEs) during the preinstrumental era requires further research, particularly as a potential analog for future climate. Using an ultrahigh resolution glacio‐chemical record from the 2013 Colle Gnifetti ice core drilled in the Swiss‐Italian Alps, we reconstructed a 2000‐year‐long summer Saharan dust record. We analyzed both modern (1780–2006) and premodern Common Era (CE) major and trace element records to determine air mass source regions to the Colle Gnifetti glacier and assess similarities to modern and reconstructed climate trends in the Northern Hemisphere. This new proxy SDE reconstruction, produced using measurements from a novel, continuous ultrahigh‐resolution (120‐μm) ice core analysis method (laser ablation‐inductively coupled plasma‐mass spectrometer) is comprised of 316, 000 data points per element covering the period 1–1820 CE. We found that the Colle Gnifetti ice core captures an anomalous increase in Saharan dust transport during the onset of the Medieval Climate Anomaly (870–1000 CE) and records other prominent shorter events (CE, 140–170, 370–450, 1320–1370, and 1910–2000), offering a framework for new insights into the implications of Saharan dust variability. Plain Language Summary: Plumes of dust from the Saharan desert transported across the Atlantic Ocean and Mediterranean Sea, influence land, ocean, and atmospheric systems, yet we know relatively little about how these events varied before the instrumental record. Saharan dust transport can result in flourishing ecosystems, poor air quality, and even changes in the frequency of North Atlantic hurricanes. In our study, we develop a summer Saharan dust event record with subannual resolution from an ice core drilled in the European Alps, dating back 2000 years. The Saharan dust record shows increased dust transport is caused by a combination of enhanced high‐pressure systems over the Mediterranean and drier conditions in Northern Africa, along with other atmospheric influences. Our record indicates the past century has seen an increased amount of Saharan dust transport, comparable to large occurrences over the past 2000 years. Additionally, we discuss implications for using our subannually resolved Saharan dust record in concert with historical records to improve interpretations of human‐climate interactions. Key Points: A well‐dated Saharan dust record, spanning 1–2006 CE, was produced using chemical analysis of an ice core from the Swiss‐Italian Alps Use of a novel, nondestructive laser ablation sampling system on ice reveals subannual resolution of dust transport to the European Alps The tenth century is characterized by continuous, large Saharan dust events, providing evidence for drier conditions in Northern Africa